Cervical Spine Manual Therapy for Aging and Older Adults. Issue 2 (April 2016) - Tudini, Frank; Chui, Kevin; Grimes, Jason; Laufer, Rachel; Kim, Sean; Yen, Sheng-Che; Vaughan, Victor
Abstract : Neck pain is a common problem in aging and older adults. This narrative review synthesizes recent literature on manual therapy to the cervical spine and adjacent regions. Emphasis has been placed on summarizing high-quality randomized clinical trials, systematic reviews with a narrative synthesis or meta-analysis, and clinical practice guidelines. The synthesis suggests that although there is limited high-quality evidence, a multimodal approach including manual therapy and exercise seems safe and effective, especially in the short term, for improving outcomes in aging and older adults with neck pain. The results for cervicogenic dizziness and headache were too varied to arrive at a firm conclusion. Additional research using consistent outcome measures is needed to establish the optimal manual therapy techniques and parameters for these common cervical conditions.